Paleoseismic Evidence of an Mw 7 Pre-Hispanic Earthquake in the Peruvian Forearc - Benavente Escobar, Carlos Lenin (2021)
We present the results of a paleoseismic survey of the Incapuquio Fault System, a prominent transpressional fault system cutting the forearc of South Perú. High-resolution Digital Elevation Models, optical satellite imagery, radiocarbon dating, and paleoseismic trenching indicate that at least 2–3 m of net slip occurred on the Incapuquio Fault generating a complex, ∼100-km long set of segmented fault scarps in the early 15th century (∼1400–1440 CE). We interpret the consistent along-strike pattern of fault scarp heights, geometries and kinematics to reflect a surface rupture generated by a single Mw 7.4–7.7 earthquake, suggesting that brittle failure of the forearc poses a significant, yet mostly overlooked, seismic hazard to the communities in coastal areas of Perú. The timing of this earthquake coincides with the collapse of the Chiribaya civilization in ∼1360–1400 CE, and we present evidence of damaged buildings along the fault trace that may be of Chiribayas age. Our surface faulting observations, when combined with observations of deformation in the forearc from geodesy and seismology, also demonstrate that the forearc in South Perú experiences a complex, time-varying pattern of permanent strain, with evidence for trench-parallel shortening, trench-parallel extension, and trench-perpendicular shortening all in close proximity but in different periods of the megathrust earthquake cycle. The kinematics of recent slip on the Incapuquio Fault are consistent with the sense of interseismic strain within the forearc measured by GPS, suggesting the fault is loaded toward failure between megathrust earthquakes.